POTENSI DAYA TARIK KAWASAN SUAKA ALAM TANJUNG BELIMBING DI DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS - Hutagalung, Bayu; Nugroho R, Joko; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2014)
Paloh sub-district in Sambas has a nature reserves called Tanjung Belimbing. It was located in the village of Sebubus. This vicinity was also recognized as a destination of nature tourist since it had a definite distinctive characteristic. This area has the potential for the beauty and the uniqueness of nature that could be developed into a tourist spot. Beside, this place was also a haven for turtles, specifically green turtles (Chelonia mydas) and hawksbill turtles (Eretmochelys imbricate) and their existence had a potential for nature tourism activities. This study aimed to assess the potential of attractiveness in Tanjung Belimbing nature reserves in the village ofÂ  Sebubus, Paloh sub-district, Sambas by means of the scoring method. Then, the result was analyzed descriptively based on the Standard Assessment and Development of Natural Attractions issued by the Commission for Co-operation and Development of Assessment of Natural Attractions in 1993. The calculation results indicated that the criteria of area attractiveness obtained was 1107,3. Accordingly it can be concluded that the attractiveness ofÂ  Tanjung Belimbing Nature reserves completely categorized as having excellent value (A) to be developed into nature tourism. Keywords : Nature reserves, nature tourism, criteria of area attractiveness